If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(-2) = 4(-2) + 1 Reorder the terms for easier multiplication: -2f = 4(-2) + 1 Multiply 4 * -2 -2f = -8 + 1 Combine like terms: -8 + 1 = -7 -2f = -7 Solving -2f = -7 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-2'. f = 3.5 Simplifying f = 3.5
| 3y-8+2y=32 | | 8-6x=38 | | 6x-19=30 | | y^3-13y^2+40=0 | | f(-2)=4x-2+1 | | 5+5x=-10 | | 5(r+3)=5t-3 | | 4x+34=8-9x | | x+9/4=x/2+2 | | 9-r=13 | | f(4)=4+-6 | | 5b-12=-2 | | x=x-4+8 | | 3X-4(X+3)=8X+6 | | x/100=1/2 | | 2x=5(x+3) | | .3x+6=12 | | Y=7x^2+5x+1 | | x^2+1=380 | | x*x+1=380 | | -9(c+7)= | | 2a+b=cx | | 6b+9=4b+29 | | -0.008x^2+1.2x-45=-245 | | 7v=2v-2 | | 4x+4/2=x+16/3 | | X-24=130 | | 2w^6y^3+4u^7w^7y^3= | | -12m+4m=11-75 | | -7(7+x)=-50 | | 2h-1/10=5/8 | | 3x^3+4x^2-32x-12=0 |